Estimation of individual heterosis in guinea pigs (Cavia porcellus) F1 crosses of Peru, Inti and Andina genotypes - Meza R., Elmer (2018)
The present study was carried out in the E.E.A. Canaan from INIA (Ayacucho, Peru) with the objective of estimating the individual heterosis in F1 guinea pigs from the crosses between the genotypes Peru (P), Andean (A) and Inti (I) for the characteristics of weight at slaughtering, growth, carcass yield, fat deposition and feed conversion. Information was obtained from 115 descendants between pure lines and crosses of the genotypes PxA, AxP and PxI, being reared as contemporary groups throughout the rearing phase. The incidence of the fixed effects of litter size, sex of the offspring and number of parturition of the mother on the variables under study was analysed through a model of fixed effects, estimating correction factors by least squares for those that had significant incidence (p<0.05). The individual heterosis was estimated as the deviation of the mean of the reciprocal cross compared to the average of the pure parents. The heterosis for the weight at slaughtering character, estimated at the level of crosses PxI (genotype Peru as a paternal route) and the reciprocal PxA, was 11.90 g (1.5%) and 10.25 g (1.3%), respectively; while the growth rate had a heterosis of 0.39 g/day (3.9%) for the PxI cross (Peru genotype as a paternal route). No appreciable levels of heterosis were observed for the other traits. It is concluded that the crossing between improved guinea pigs does not produce significant levels of individual heterosis at the level of the characters related to meat production.